Rekognisi Ḥadīṡ Iftirāq Dalam Ruang Multikultural - Miski Miski (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
The purpose of this research is to analyze two main things, namely how the iftiraq hadith is used as a tool to legitimize the existence of other groups, and how to actualize this hadith in multicultural life. This research also uses a fiqh al-ḥadīṡ approach with a descriptive-hermeneutical analysis model. This research has shown two things. First, the concepts of "According to the Prophet and the Companions" and "al-Jamā'ah" have been 'withdrawn' to monopolize the concept of salvation for a particular religious group. Second, in the context of multicultural life, iftirāq hadith needs to be seen as a text that is connected to other texts, namely, the Qur'an and other hadiths. In this case, there needs to be a distinction between the principles of belief and the principle of coexistence. The principle of belief becomes vertical: man and God; while the principle of coexistence is horizontal: humans and their environment. This principle have consequences for the importance of maintaining human values ​​and others for the sake of a peaceful, balanced and harmonious life.